Entre el hogar y el aula: familia y rendimiento académico - Torres Velázquez, Laura Evelia (2026)
Academic performance (AP) in university education is a complex and multifactorial phenomenon, influenced by a diversenetwork of personal, family, social, and institutional variables. Various studies reveal that the family environment emergesas the most significant variable through perceived support, communication, functionality, socioeconomic status, and theeducational capital of the parents. The family serves as the primary source of social support; consequently, having a positive and functional family climate correlates directly with better academic achievement and performance.Therefore, the objective of the present study was to analyze the relationship between the perceptions of young universitystudents regarding their family environment and their academic performance. The participants consisted of 587 studentsfrom six degree programs at a Faculty of the UNAM. Two instruments were administered: the Scale to Evaluate the Intrafamily Environment (ERI) and the School Activities Questionnaire. The results highlight the aspects of the family environment related to academic performance (such as perceptions of support, acceptance, communication, affection,and validation of opinions, among others). Furthermore, the study identifies family factors (acceptance, support, interest in studies), personal factors (interest, motivation to study, assignments, perception of emotional and affective support), and school factors (scholarships, time for assignments, work commitments) that either facilitate or hinder academic performance. These findings allow us to provide key elements to influence the improvement of educational outcomes foruniversity students.